Performance of Customs and Excise Supervision at the Sea Border - Fadli Rahman; Femmy M.G. Tulusan; Johny R.E. Tampi (Journal of Public Administration and Government, 2023)
Sangihe Archipelago Regency consists of small islands, both inhabited and uninhabited, surrounded by the ocean. The existence of these islands has the potential to become a route for entry and exit for the smuggling of goods into the territory of the Unitary State of the Republic of Indonesia, which in turn is not only to the economy but also to national defense and security. The Directorate General of Customs and Excise, as one of the agencies mandated by law to guard the border areas of the country, must play a role in protecting the environment and society from the threat of certain goods and contributing to state revenues to support national financing to realize an advanced Indonesia. In this study, the research object that is the focus of the author is the sea border area between Indonesia and the Philippines, and what will be analyzed is the supervisory performance of the North Sulawesi Regional Office of the Directorate General of Customs and Excise in the border region. The purpose of this study is to analyze the performance of the supervision carried out by the Regional Office of the Directorate General of Customs and Excise in North Sulawesi in the sea border area between Indonesia and the Philippines. A descriptive method with a qualitative approach is used in this study. Based on the findings of this study, the supervision performance of regional offices of the Directorate General of Customs and Excise is still not optimal, which is influenced by several factors such as geographical conditions, human resources, and facilities and infrastructure.